RECOGNITION OF SOCIETY RIGHTS IN TRADITION SPECIALLY IN TOURISM REGULATION BASED ON ARTICLE 18B PARAGRAPH (2) OF THE 1945 CONSTITUTION OF THE REPUBLIC INDONESIA - Yuliartini, Ni Putu Rai; Mangku, Dewa Gede Sudika; Adnyani, Ni Ketut Sari (Journal Equity of Law and Governance, 2021)
This research is focused on the normative problem of the vacuum of recognition norms by customary law communities which causes injustice in tourism development. This research is a normative legal research with a socio legal approach. This research approach uses a statutory approach, a legal approach with a policy orientation. The absence of norms at the level of the Law, plus contradictory interpretations regarding the conditions in Article 18B paragraph (2). At the local government level, the province of Bali has actually made a number of legal products that recognize indigenous peoples in the tourism sector. It is not sufficient to prove the recognition of indigenous peoples in one area. East Java Provincial Regulation as a comparative study. The results show that the recognition of customary law communities is still included in the product of tourism regulations. It affects ± 60% minimum operational funds, ± 15% low sharing funds, ± 10% local government contributions, and ± 5% sourced from sponsors. Regarding this fact, the alternative solution is through the reconstruction of the ideal legal model for the recognition of customary law communities in the tourism sector as a legal input for drafters.